Evaluasi Sensori Produk Makanan dan Minuman Berbahan Dasar Honje Sebagai Upaya Pengembangan Produk - Ni Gusti Made Kerti Utami; Ratih Pitria Purnamasari; Maksum Suparman; Dodi Affandi (Tourism Scientific Journal, 2023)
This research aims to conduct a sensory evaluation of food and beverage products made from honje, which are the result of development. Honje was only used as Honje juice but was developed into several food and beverage products, namely Honje Butter Cookies, Honje Jam, and Mojito Honje (Monje). These food and beverage products are selected from the identification of agricultural products in the Cisangkal Tourism Area. They have their own uniqueness and the potential to be developed because they have a lot of resources and are easy to implement. The research method used is descriptive quantitative through organoleptic tests on 4 sensory aspects, namely: Color, Aroma, Taste/Like, and Texture related to Honje-based food and beverage products, assisted by respondents in Cisangkal, Pangandaran and surrounding areas who will become target consumers as many as 30 people. The results of this evaluation will provide additional confirmation to the local community that Honje Laka, which is owned by almost the entire community there, can increase self-confidence, and the economy and ultimately help the Cisangkal Tourism Area develop even better. This research was carried out to be a continuation of research activities and community service in the Cisangkal Tourism Area.